Hubungan Antara Standar Kredit, Struktur Piutang, Dan Kinerja Keuangan Dalam Manajemen Piutang Perusahaan - Tsinta Dewi Aryaningtyas; Ni Putu Ayu Sinta; Maulana Ikhrom Ababil; Maria Yovita R. Pandin (Universitas Merdeka Madiun, 2025)
The purpose of this study is to analyze the relationship between credit standards, receivables structure, and financial performance on receivables management of companies in the transportation services sector listed on the Indonesia Stock Exchange (IDX). The research method used is a quantitative approach with a correlation research type. Secondary data obtained from the company's financial statements, namely PT. Blue Bird Tbk, PT. Adi Sarana Armada Tbk, PT. Armada Berjaya Trans Tbk, and PT. AirAsia Indonesia Tbk. Variables include credit standards (measured by Credit Risk Ratio (CRR)), receivables structure (measured by Average Collection Period (ACP)), financial performance (measured by Return On Assets (ROA)) and receivables management (measured by Receivables Turnover Ratio (RTR)). The results of the classical assumption test indicate that the regression model used is free from multicollinearity and heteroscedasticity problems and meets the assumption of normal distribution. In addition, the results of the simultaneous test show that the three independent variables, namely credit standards, receivables structure and financial performance have a significant effect on financial management. This research contributes to company management in determining more selective credit policies and accounts receivable management in order to improve overall financial efficiency